Improving asphalt concrete durability through soda lignin powder - Aya K. Albayati; Amjad H. Albayati (Transportation Engineering)
Lignin has emerged as a promising asphalt binder modifier due to its sustainable and renewable nature, with the potential to improve flexible pavement performance. This study investigates the use of Soda Lignin Powder (SLP), derived from Pinus wood sawdust via alkaline treatment, as an asphalt modifier to enhance mixture durability. SLP was characterized using Fourier Transformation Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy with Energy Dispersive X-ray Analysis (SEM/EDX), revealing significant changes in its chemical structure post-extraction. These analyses showed the presence of phenolic units, including hydroxyphenyl propane, syringyl, and guaiacyl units. The morphology of SLP was identified as irregular and spherical particles consisting of carbon, oxygen, nitrogen, and sulfur. Experimental evaluations involved three SLP dosages (2 %, 4 %, and 6 % by weight of asphalt binder), with tests for penetration, softening point, ductility and rotational viscosity. Additionally, the asphalt mixtures were tested for their performance in terms of moisture susceptibility, resilient modulus, permanent deformation, and fatigue resistance. Results indicated that SLP effectively reduces the temperature susceptibility of asphalt by increasing its stiffness and rotational viscosity. Furthermore, mixtures with 6 % SLP showed enhanced moisture resistance, with a Tensile Strength Ratio (TSR) of 86.98 %, a 74.1 % reduction in accumulated permanent deformation at 10,000 cycles, and a 38.1 % increase in the Cracking Tolerance Index (CT index) compared to the control mix (0 % SLP content). These findings confirm that SLP has the potential to be an effective additive in the design of asphalt mixture. Moreover, it allows producing endurable mixtures with higher resistance to distress.